Special Protection of Human Rights of Children II.: Legislative History of the UN Convention on the Rights of the Child - Samardžić, Sandra O. (International Children’s Rights, 2024)
It took a long journey to recognise and regulate children’s rights institutionally. Today, numerous organisations are promoting measures that exclusively regulate the position of children; that is, acts which indirectly affect children’s rights. The intent of these acts is not uniform in terms of whether they are legally binding or not, and neither is their relevance, however, it is certain that once this process has been initiated, the manner in which children and their positions will be perceived will become permanently set. Regarding family law, that is, child law, the most significant act to be passed was the adoption of the UN Convention on the Rights of the Child in 1989.1 The Convention stems from years of research. The early stages of the work on a document dealing with children’s rights were prompted by advances in perceiving children as separate individuals, and by the accelerated consolidation of the International Human Rights Law.2 In the 34th session of the UN Commission on Human Rights in 1978, the degree to which children suffered during armed conflicts and other forms of aggression was specifically stressed, along with the need to protect them and their position. In the same session, the Polish delegation submitted a draft proposal for the Convention on the Rights of the Child (Polish draft), which was based on the 1959 United Nations Declaration on the Rights of the Child. Shortly afterwards, a working group was formed that dealt with the proposals submitted by various States or organisations. More than ten years would pass before the working group submitted the final draft (although the initial plan was that the Convention be adopted in 1979), which was first adopted by the UN Human Rights Commission and the Economic and Social Council. Thereafter, it was submitted to the UN General Assembly for adoption, where it was adopted by acclamation.3 The Convention on the Rights of the Child represents a unified and coordinated document, whereas the rights proclaimed in the Convention represent a synthesis of efforts to ensure the child’s best possible quality of life. Although the final regulation of children’s rights and its attempt to improve the overall position of children are undeniably motivated by a noble idea, it was certainly not easy to implement it. Keywords: children’s rights, convention, children’s rights history